A possible desensitized state conformation of the human α7 nicotinic receptor: A molecular dynamics study - Chiodo, L.; Malliavin, T.E.; Maragliano, L.; Cottone, G. (Biophysical chemistry, 2017)
The determination of the conformational states corresponding to diverse functional roles of ligand gated ion channels is subject of intense investigation with various techniques, from X-rays structure determination to electrophysiology and computational modeling. Even with a certain number of structures becoming recently available, only few major structural features distinguishing conductive open channel from the non conductive resting protein have been highlighted, while high-resolution details are still missing. The characterization of the desensitized conformation(s) is even more complex, and only few specific characteristics have been identified. Furthermore, experimental data provide conflicting information for different ion channels, adding further complexity to the topic. Desensitization is defined as the transition of the agonist-bound open channel into an ion channel configuration inactive even in the presence of agonists. In this work, we analyze a conformation corresponding to a non conductive state obtained via molecular dynamics simulations of a homology model of the human α7 nicotinic receptor complexed with agonists. We highlight some characteristics that could associate it to a desensitized state. The obtained structure is assessed against experimental data for other ligand gated ion channels that have been putatively associated to active, inactive and desensitized conditions. [Display omitted] •The structure of desensitized ion channels is scarcely characterized.•These channels are non conductive, agonist-bound, with a peculiar LBD-TMD interface.•We propose a desensitized form of human α7 nAChR based on homology modeling and MD.•The structure is assessed against experimental data on desensitized LGICs.